Extractive distillation configuration for nitric acid dehydration using sulfuric acid as a solvent - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Industrial & Engineering Chemistry Research, 2020)
In this work, an extractive distillation configuration for dehydration of nitric acid is proposed with sulfuric acid as a solvent. Thermodynamic modeling of the vapor-liquid equilibrium of binary and ternary systems of nitric acid/water/sulfuric acid is carried out using the electrolyte non-random two-liquid (eNRTL-RK) thermodynamic property method in the Aspen plus process simulator. The model performance is validated by comparing the experimental data with the estimated data by the eNRTL-RK model and is found to be in good agreement. The thermodynamic model is then used for developing a triple-column extractive distillation sequence, comprising a preconcentration column, an extractive distillation column, and a solvent recovery column. The configuration is designed, simulated, and optimized to concentrate dilute nitric acid using sulfuric acid as a solvent to break the nitric acid-water azeotrope. The operating and structural parameters of the distillation configuration are optimized simultaneously with an objective of minimizing the energy consumption and the total annual cost (TAC) of the overall configuration.